The human brain in a high altitude natural environment: A review - Zhang, Xinjuan; Zhang, Jiaxing (Frontiers in Human Neuroscience, 2022)
With the advancement of in vivo magnetic resonance imaging (MRI) technique, more detailed information about the human brain at high altitude (HA) has been revealed. The present systematic review aimed to draw a conclusion regarding changes in the human brain in both unacclimatised and acclimatised states in a natural HA environment. Using multiple advanced analysis methods that based on MRI as well as electroencephalography, the modulations of brain gray and white matter morphology and the electrophysiological mechanisms underlying processing of cognitive activity have been explored in certain extent. The visual, motor and insular cortices are brain regions seen to be consistently affected in both HA immigrants and natives. Current findings regarding cortical electrophysiological and blood dynamic signals may be related to cardiovascular and respiratory regulations, and may clarify the mechanisms underlying some behaviours at HA. In general, in the past ten years, researches on the brain at HA have gone beyond cognitive tests. Due to the sample size is not large enough, the current findings in HA brain are not very reliable, and thus much more researches are needed. Moreover, the histological and genetic bases of brain structures at HA are also needed to be elucidated.